Analysis of the protein related receptor GPR92 in G-cells - Rettenberger, Amelie T.; Schulze, Waltraud; Breer, Heinz; Haid, Désirée (Frontiers in Physiology, 2015)
A continuous assessment of ingested food in the gastric lumen is essential for fine-tuning the digestive activities, including the secretion of the regulatory hormones such as gastrin. It has been proposed that G-cells may be able to sense the amount of ingested proteins and adjust the secretion of gastrin accordingly. Our previous studies have shown that G-cells express suitable receptor types, most notably the peptone-receptor GPR92 and the amino acid receptors GPRC6A and CaSR; however, their relative importance remained unclear. To determine the relative quantity of each receptor type, individual G-cells isolated from the transgenic mouse line mGas-EGFP were analyzed by means of a Liquid Chromatography Tandem-Mass Spectrometry (LC-MS/MS) procedure. The results indicate that the relative amount of receptor protein for GPR92 was much higher than for the receptor types GPRC6A and CaSR. These findings support the notion that the peptone-receptor GPR92 may be particularly relevant for sensing partially digested protein products. This view was supported by the finding that a high-protein diet affected the expression level of the peptone-receptor GPR92 in the gastric antrum as well as in the circumvallate papillae.